Older, Church-Going African Americans' Attitudes and Expectations About Formal Depression Care. (January 2018) - Wharton, Tracy; Watkins, Daphne C.; Mitchell, Jamie; Kales, Helen
This phenomenological study involved focus groups with church-affiliated, African American women and men ( N = 50; ages 50 and older) in southeast Michigan to determine their attitudes and expectations around formal mental health care. Data analysis employed a constant comparative approach and yielded themes related to formal mental health care, along with delineating concerns about defining depression, health, and well-being. Health and well-being were defined as inclusive of physical and spiritual aspects of self. Churches have a central role in how formal mental health care is viewed by their attendees, with prayer being an important aspect of this care. Provider expectations included privacy and confidentiality; respect for autonomy and need for information, having providers who discuss treatment options; and issues related to environmental cleanliness, comfort, and accessibility. Implications include providing effective, culturally tailored formal depression care that acknowledges and integrates faith for this group.